DNA [videorecording (DVD)] : the amazing double helix - Conway, Seth; Soare, Thomas F. (Thomas Fulton), 1936- (Educational Video Network, 2005)
Defines DNA, examines its structure, explains how it functions in the human body, and discusses its role in the field of genetic engineering. Study questions are included on disc.